Examining Longitudinal and Concurrent Links Between Writing Motivation and Writing Quality in Middle School. (January 2023) - Rasteiro, Isabel; Limpo, Teresa
Research shows that writing motivation decreases throughout schooling and predicts writing performance. However, this evidence comes primarily from cross-sectional studies. Here, we adopted a longitudinal approach to (a) examine the development of attitudes toward writing, writing self-efficacy domains, and motives to write from Grade 6 to 7, and (b) test their longitudinal and concurrent contribution to the quality of opinion essay in Grade 7, after controlling for quality in Grade 6. For that, 112 Portuguese students completed motivation-related questionnaires and composed two opinion essays in Grade 6 and 1 year later, in Grade 7. Findings showed that, while attitudes and all motives to write declined, self-efficacy did not. Additionally, opinion essay quality in Grade 7 was associated with essay quality in Grade 6 as well as with self-efficacy for self-regulation and intrinsic motives in Grade 7. In other words, current motivational beliefs seem more important to students' writing quality than their past beliefs. This conclusion means that, in order to fostering students' writing performance, middle-grade teachers should nurture their positive beliefs about writing by placing a higher value on writing motivation in the classroom.